2004
DOI: 10.1016/j.jasms.2004.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Binding energies of water to lithiated valine: Formation of solution-phase structure in vacuo

Abstract: Dissociation kinetics for loss of a water molecule from hydrated ions of lithiated valine, alanine ethyl ester and betaine are determined using blackbody infrared radiative dissociation at temperatures between Ϫ60 and 110°C. From master equation modeling of these data, values of the threshold dissociation energy are obtained for clusters containing one through three water molecules. By comparing the values for valine with its two isomers, one a model for the nonzwitterion structure, the other a model for the z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
102
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(110 citation statements)
references
References 65 publications
7
102
1
Order By: Relevance
“…It is quite clear from Table 1 that the addition of one water molecules to -NO/-OO coordination modes of Ala-M + /ZAla-M + complexes at the metal ion end does not stabilize the -OO coordination mode of ZAla-M + complex in gas phase. The observed trend of stability by the addition of one water molecule in above discussed coordination modes is consistent with trend of stability reported in the previous studies [58][59][60]. Now, we have considered same coordination sites for dihydrates of -NO/OO/OH coordination modes as we have taken in the case of monohydrates.…”
Section: Methodssupporting
confidence: 89%
“…It is quite clear from Table 1 that the addition of one water molecules to -NO/-OO coordination modes of Ala-M + /ZAla-M + complexes at the metal ion end does not stabilize the -OO coordination mode of ZAla-M + complex in gas phase. The observed trend of stability by the addition of one water molecule in above discussed coordination modes is consistent with trend of stability reported in the previous studies [58][59][60]. Now, we have considered same coordination sites for dihydrates of -NO/OO/OH coordination modes as we have taken in the case of monohydrates.…”
Section: Methodssupporting
confidence: 89%
“…[1][2][3][4] In living cells, free metal cations provide electrochemical gradients required for cellular function and they also serve as messengers. It is found that metal ion-amino acids interaction is responsible for the enzyme activity and stability of the protein structure.…”
Section: Introductionmentioning
confidence: 99%
“…The nature of the metal cation (Li + , Na + , and K + ) interaction has been investigated experimentally and theoretically with valine and glycine in presence and absence of water molecules. [1,4,27,[31][32][33] In their study it has been found that the metal cations are coordinated to the non-zwitterionic structure via the nitrogen as well as carbonyl oxygen (-NO coordination), whereas for the zwitterionic structures the coordination is held to the oxygen atoms (-OO coordination). Further, it is also found that the addition of a single water molecule does not significantly affect the relative energies calculated for the valine-cation complex.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2,9 Salient characteristics of peptoids include their robust higher-order structure, folding dynamics, increased resistance to denaturation relative to proteins, and the means by which the structure and interactions can be intelligently designed by the primary sequence of the chain. 2,3,[10][11][12] Previous methods of studying peptides and peptoids have included circular dichroism of oligomers, 5,11,13 infrared spectroscopy, 12 NMR, 11 mass spectrometry, 14,15 and computational modeling; 16,17 these methods primarily focused on design and characterization of the secondary structure.…”
Section: Introductionmentioning
confidence: 99%